Design and introduction of a quality of life assessment and practice support system: perspectives from palliative care settings - Richard Sawatzky; Esther Laforest; Kara Schick-Makaroff; Kelli Stajduhar; Sheryl Reimer-Kirkham; Marian Krawczyk; Joakim Öhlén; Barbara McLeod; Neil Hilliard; Carolyn Tayler; S. Robin Cohen (SpringerOpen, 2018)
Abstract Background Quality of life (QOL) assessment instruments, including patient-reported outcome measures (PROMs) and patient-reported experience measures (PREMs), are increasingly promoted as a means of enabling clinicians to enhance person-centered care. However, integration of these instruments into palliative care clinical practice has been inconsistent. This study focused on the design of an electronic Quality of Life and Practice Support System (QPSS) prototype and its initial use in palliative inpatient and home care settings. Our objectives were to ascertain desired features of a QPSS prototype and the experiences of clinicians, patients, and family caregivers in regard to the initial introduction of a QPSS in palliative care, interpreting them in context. Methods We applied an integrated knowledge translation approach in two stages by engaging a total of 71 clinicians, 18 patients, and 17 family caregivers in palliative inpatient and home care settings. Data for Stage I were collected via 12 focus groups with clinicians to ascertain desirable features of a QPSS. Stage II involved 5 focus groups and 24 interviews with clinicians and 35 interviews with patients or family caregivers during initial implementation of a QPSS. The focus groups and interviews were recorded, transcribed, and analyzed using the qualitative methodology of interpretive description. Results Desirable features focused on hardware (lightweight, durable, and easy to disinfect), software (simple, user-friendly interface, multi-linguistic, integration with e-health systems), and choice of assessment instruments that would facilitate a holistic assessment. Although patient and family caregiver participants were predominantly enthusiastic, clinicians expressed a mixture of enthusiasm, receptivity, and concern regarding the use of a QPSS. The analyses revealed important contextual considerations, including: (a) logistical, technical, and aesthetic considerations regarding the QPSS as a technology, (b) diversity in knowledge, skills, and attitudes of clinicians, patients, and family caregivers regarding the integration of electronic QOL assessments in care, and (c) the need to understand organizational context and priorities in using QOL assessment data. Conclusion The process of designing and integrating a QPSS in palliative care for patients with life-limiting conditions and their family caregivers is complex and requires extensive consultation with clinicians, administrators, patients, and family caregivers to inform successful implementation.